Inovasi Pencatatan Akuntansi Berbasis Whatsapp dengan Integrasi Artificial Intelligence pada UMKM Buen Kanam Balikpapan - Prihanisetyo, Adi; Oeij, Karmilla Sumitro; Khaerunissa, Khaerunissa; Nurul Talita Sabela; Anggreani Umasangaji (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2026)
The Innovation Development Program conducted by Group 2 in Gunung Sari Ulu Village consisted of a structured series of mentoring activities designed to strengthen the financial literacy and marketing capabilities of local UMKM. The program focused on guiding participants in recording simple cash flow using the Monly AI application, which helped them understand how Artificial Intelligence can support more accurate and organized financial management. In addition, participants were taught how to properly separate incoming and outgoing transaction notes so that their business finances could be monitored more clearly and systematically. The program also introduced strategies for promoting products through digital marketing, enabling UMKM to expand their market reach by utilizing online platforms and creating more appealing promotional content. Overall, this activity aimed to broaden the participants’ knowledge of AI-based financial recording while also equipping them with practical marketing skills needed to increase visibility and attract consumer purchasing power. By integrating technology with improved marketing practices, the program sought to empower UMKM to operate more efficiently, enhance their competitiveness, and strengthen the sustainability of their business activities within the local community.